Dialectical behavior therapy - Chapman, Alexander L. (Alexander Lawrence); Dixon-Gordon, Katherine L. (Theories of psychotherapy series., 2020)
"This book reviews the theoretical underpinnings and practice of dialectical behavior therapy (DBT), a treatment developed by Marsha Linehan to help complex clients, such as suicidal individuals and those with borderline personality disorder (BPD) and related problems. DBT has proven to be effective with a range of mental health issues that are often difficult to treat, including nonsuicidal self-harm, substance abuse, and eating disorders. DBT is a behavioral treatment that views emotion dysregulation as being the core of BPD and other disorders. Through regular individual therapy, group sessions, and phone coaching, therapists support clients while challenging them to learn more adaptive behaviors for managing their emotions as well as new life skills. In DBT, therapists also support each other by forming consultation teams. In addition to reviewing standard DBT, this book describes its applications and adaptations for various populations and settings. Case material demonstrates how to apply all elements of the DBT process in realistic clinical scenarios"--